The Islamic State and Thomas Hobbes: Views on the State, Law, and the Role of Religion - Sugara, Robi; Fitriyanti, Rahmi; Idris, Faisal Nurdin (Jurnal Ilmu Sosial Indonesia (JISI), 2024)
Abstract. This article explains the concept of an Islamic state from the perspective of Thomas Hobbes' book Leviathan. Although Hobbes does not explicitly discuss the Islamic state, the basic principles of his theory of the absolute state, natural law, and the role of religion in a state provide a framework that can be used to explain the basic principles of the Islamic state. This article uses a qualitative approach with textual analysis methods on Hobbes' major work, Leviathan, as well as relevant literature on the concept of an Islamic state. Based on critical and interpretive readings of the text, this paper identifies and analyses the main themes related to absolute power and the role of religion in governance according to Hobbes. This analysis highlights how a state applying Islamic law (Sharia) can be compared to the concept of the state from a Hobbesian perspective, particularly in terms of absolute power and religious regulation to maintain order and peace. This article also discusses the relevance of Hobbes' natural law in the context of Islamic law and how the principles of universal justice and morality are applied. The findings of this article show that although there are fundamental differences in the sources of legitimacy and the role of religion, the basic principles of Hobbes' theory remain relevant in understanding the dynamics that occur in Islamic states, particularly in the modern world. Keywords: Islamic State, Thommas Hobbes, Islamic Sharia, Power and Authority. Abstrak. Artikel ini menjelaskan konsep negara Islam dalam perspektif Thomas Hobbes melalui buku Leviathan. Meskipun Hobbes tidak secara eksplisit membahas negara Islam dalam bukunya, namun prinsip dasar teorinya tentang negara absolut, hukum alam, dan peran agama dalam suatu negara memberikan kerangka yang dapat digunakan untuk menjelaskan pengertian negara Islam. Artikel ini menggunakan pendekatan kualitatif dengan metode analisis tekstual terhadap karya utama Hobbes, Leviathan, serta literatur yang relevan mengenai konsep negara Islam. Berdasarkan pembacaan teks secara kritis dan interpretatif, tulisan ini mengidentifikasi dan menganalisis tema-tema utama terkait kekuasaan absolut dan peran agama dalam pemerintahan menurut Hobbes. Analisis ini menyoroti bagaimana negara yang menerapkan hukum Islam (syariah) dapat dibandingkan dengan konsep negara dalam perspektif Hobbesian, khususnya dalam hal kekuasaan absolut dan peraturan agama untuk menjaga ketertiban dan perdamaian. Artikel ini juga membahas relevansi hukum alam ala Hobbes dalam konteks hukum Islam dan bagaimana prinsip keadilan dan moralitas universal diterapkan. Hasil artikel ini menunjukkan bahwa meskipun terdapat perbedaan mendasar dalam sumber legitimasi dan peran agama, namun prinsip dasar teori Hobbes tetap relevan dalam memahami dinamika yang terjadi di negara-negara Islam, khususnya di dunia modern. Kata Kunci: Negara Islam, Thommas Hobbes, Hukum Syariah, Kekuasaan dan Otoritas.